The Relationship Between Workload, Discipline And Compensation Towards Employee Job Satisfaction - Zainal Ruma; Anang Setiawan (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study aims to examine the relationship between workload, work discipline, and compensation and their joint effect on employee job satisfaction at PT Kinarya Utama Teknik, an information technology infrastructure company based in Makassar. The research employs an associative quantitative design using a survey method. Primary data were collected through structured questionnaires from 70 permanent employees selected using proportioned stratified random sampling. The data were analyzed using multiple linear regression with the support of SPSS version 26, complemented by F-tests, t-tests, and the coefficient of determination (R²) to test the research hypotheses. The results show that workload, work discipline, and compensation simultaneously have a significant effect on employee job satisfaction, with an Adjusted R² value of 0.828, indicating that 82.8% of the variance in job satisfaction is explained by the three independent variables. Partially, workload, work discipline, and compensation each have a positive and significant influence on job satisfaction, as indicated by t-values that exceed the critical t-table value and significance levels below 0.05. These findings suggest that a balanced workload, consistent and fair application of discipline, and adequate, equitable compensation schemes are key determinants of employees’ satisfaction in a high-demand technical work environment. The study provides important implications for human resource management, highlighting the need for organizations to design integrative policies on workload distribution, disciplinary systems, and compensation packages to enhance job satisfaction and support sustainable employee performance. Future research is recommended to include additional variables such as leadership style, work environment, and career development to obtain a more comprehensive model of job satisfaction.